Provable Data Possession Schemes from Standard Lattices for Cloud Computing. (9th December 2021) - Luo, Fucai; Al-Kuwari, Saif; Lin, Changlu; Wang, Fuqun; Chen, Kefei
Abstract: Provable Data Possession (PDP) is of crucial importance in public cloud storage since it allows users to check the integrity of their outsourced data without downloading it. However, the existing PDP schemes, which are based on classical number-theoretic assumptions, are insecure under quantum attacks. In this paper, we propose the first PDP scheme from standard lattices, using a specific leveled fully homomorphic signature (FHS) scheme. To remove the complex key management of PDP cryptosystem on the public key infrastructure (PKI) setting, we employ a specific leveled identity-based (ID-based) FHS scheme to construct the first ID-based PDP scheme from standard lattices. Our two PDP schemes are secure under the standard small integer solution (SIS) assumption, which is conjectured to withstand quantum attacks. Furthermore, we conduct experimental evaluations to validate the feasibility of the proposed PDP schemes in practice.